BEST INTEREST OF THE CHILD IN ADOPTION CASES, PROBLEMATIC ISSUES OF SURROGATE ADOPTION - Kadi, Xhensila (European Scientific Journal, ESJ, 2015)
The best interest of the child has long been in the center of attention of the legislator in almost every state. It may happen that, for the most varied reasons, a child is deprived of the biological parents. In such a situation, the adoption, as one of the sources of the family relationship, is often considered with interest. The adoption is a legal transaction, which is based on the mutual wills of the subjects that participate in it, and, as a result, it is constituted a new legal relationship between the adopted child and the adopter parents. So, in adoption cases, we are dealing with civil kinship which replaces the biological relationship between the adoptee and the original family. Relying on the fact that the adoption is an act of special importance, the legislator requires the respect of legal requirements necessary for a more efficient adoption. Regarding the administrative and judicial procedure through which the process of adoption passes, we note that the adoption is authorized only by the competent authority, the Albanian Adoption Committee, and it is finalized by the Court. The whole process is guided by a principle, the best interest of the child. It is expressly provided in Article 240 of the Family Code, according to which the adoption is allowed only if it is in the best interest of the child, and guarantees the respect for his fundamental rights. Therefore, the adoption should be carried out in accordance with the legal requirements and proceedings that guarantee the rights of child, the rights of the biological parents and the rights of the adoptive parents. In all the judicial proceedings regarding to the child, an important role is played by the psychologist, as a professional that assess the situation in the case of administrative proceedings, as well as in the court proceedings. This paper aims to present the Albanian legal framework regarding the institution of adoption, reflecting the conditions that should be accomplished for the realization of the adoption and its efficiency. In the paper we will also focus on some issues that may arise in the case of the surrogate adoption.